Employee Payroll Accounting Application Using Extreme Programming Development Method - Ramadhani, Nafi; Hidayatulloh, Syarif (JURNAL TEKNIK KOMPUTER AMIK BSI, 2025)
Technology allows company structures to become more effective and efficient for payroll system applications, as almost all parts of the company have adopted this technology. One such company, PT. Langgeng Engineering Tehnik Indonesia, which produces and sells spare parts, has an HR department responsible for managing extensive employee data, including payroll data. The process is currently done manually with the help of Microsoft Excel, requiring a high level of accuracy and being very prone to errors. The most significant issue is certainly payroll management, as it relates to the company's finances and employee welfare. To reduce the risk of errors in managing this data, particularly payroll, this research aims to contribute by creating a payroll application designed to facilitate management in processing and disbursing salaries to every employee working in the company, while also minimizing the risk of errors in management. The application is built using the Extreme Programming method, which offers advantages in terms of rapid development, efficiency, adaptability, and flexibility. This application is developed as a desktop-based solution using Java programming language, as its users are limited and it is intended for internal company use. The application is tested using Black Box testing, a technique that evaluates the functionality without considering the internal structure of components or systems. The testing is conducted with eight scenarios, and all tests yield valid results.